The Effect of the Drill Method in Improving Smash Accuracy in Badminton Games - Ridho, Dimas Muhammad; Sukardi, Sukardi; Junaidi, Ilham Arvan (JURNAL PENDIDIKAN OLAHRAGA, 2026)
The results of observations in PB. Fajar Cempako there are many players who are not able to smash by positioning balls that can kill the opponent, so the opportunity to score points through smash is less than optimal. Most players show limitations in mastering basic smash techniques, such as body position, contact time with the shuttlecock, and wrist control. This study aims to determine the influence of the drill method in increasing the accuracy of smash in badminton games in PB clubs. Dawn of Cempako. The research method used in this study is an experimental method with a preexperimental type. The study population was 10 athletes with research sampling using total sampling. The data collection technique used a badminton smash accuracy test. The data analysis techniques used were normality tests, homogeneity tests, and hypothesis tests using an independent t-test type of samples t test assisted by spss 25 for windows. The results of the study showed that there was an influence of drill method training in improving the accuracy of badminton game smash in PB clubs. Fajar Cempako is seen from the tcal value of 6.943 > ttable of 2.228 and the value of sig. 0.000 < 0.05. The percentage of the effect of drill method training in improving the accuracy of badminton game smash in PB clubs. Fajar Cempako by 87%. From these results, it can be concluded that drill method training can improve the accuracy of athletes' smash with good and accurate smash accuracy.